Pengembangan Chatbot Untuk Layanan Pimpinan Daerah Muhammadiyah Kota Yogyakarta Menggunakan Metode Rule-based - Dewi Soyusiawaty; Febi Ganda Putra (LPPM STIKOM Tunas Bangsa, 2023)
The use of information systems such as the Web is common in institution service processes and information media. The Muhammadiyah Regional Leadership (PDM) in Yogyakarta uses the web information system as a useful media service to provide services and information to the general public. However, when using these web services, the question-and-answer process is not yet effective in providing maximum service, as there are some system limitations in providing performance in the form of quick access. Chatbots are solutions that you can use to answer questions and answers problem. The development of this chatbot can support efforts to improve the service by responding quickly and accurately to questions according to user expectations. In this study, chatbot development uses the Rule-based method as a knowledge base. Based on the results of the tests performed, the accuracy value is 91.97%.